Estudos sobre a deterioração fúngica no segmento de panificação - Garcia, Marcelo Valle (2020)
Bread is one of the oldest and most consumed foods in the world and its contamination by filamentous fungi is related to economic losses. The investigation of the causes and the main species responsible for the spoilage of these foods, as well as effective control measures must be clarified. Therefore, the objective of this work was to investigate and identify the sources of the main fungi present in the industrial environment and bakeries involved in the spoilage of bread. Furthermore, to evaluate control measures through organic acids. Our study showed that in Brazil, the main type of bread consumed is the “French bread” and, among those interviewed, most discard bread when one of the slices is visibly moldy. In addition, the green/blue mold is the most observed throughout the Brazilian territory. In a medium-sized industry, Penicillium Roqueforti (Green mold) and Hyphopichia burtonii (White mold) were the main species responsible for the spoilage of sliced bread and these fungi were also present in the raw materials used in the production of these foods, as well as in the environmental air of processing sites. Despite being present in the raw materials and being responsible for the spoilage, our study revealed that contamination by P. roqueforti and Penicillium paneum is reduced during baking. In bakeries, a low correlation was found between good manufacturing practices and fungal air contamination in these establishments. Moreover, potassium sorbate was more effective in the inhibition of isolated strains from moldy bread than calcium propionate, and Paecilomyces variotti (PV10) was the most resistant fungus even at the highest concentrations of preservatives (128 mM). Finally, care with the quality of raw materials as well as the correct hygiene of environmental air are alternatives for the control of fungal contamination and consequent increase in the shelf life of bread, once the isolated strains of moldy bread proved to be resistant to the tested preservatives.